A Reverse Strategy to Restore the Moisture‐deteriorated Luminescence Properties and Improve the Humidity Resistance of Mn4+‐doped Fluoride Phosphors. Issue 20 (16th September 2020) - Liu, Lili; Wu, Di; He, Shengan; Ouyang, Zejian; Zhang, Junfei; Du, Fu; Peng, Jiaqing; Yang, Fengli; Ye, Xinyu
Abstract: Fluoride phosphors as red components for warm white LEDs have attracted a tremendous amount of research attention. But these phosphors are extremely sensitive to moisture, which seriously limits their practical industrial applications. To tackle this problem, unlike all the straightforward preventive strategies, a reverse strategy "Good comes from bad" was successfully developed to treat the degraded K2 SiF6 : Mn 4+ (D‐KSFM) phosphor in the present study, which not only completely restores the luminescence properties, but also significantly enhances the moisture resistance at the same time. After treatment with an oxalic acid solution as restoration modifier, the emission intensity of the D‐KSFM phosphor can be restored to 103.7% of the original K2 SiF6 : Mn 4+ red phosphor (O‐KSFM), and the moisture resistance is remarkably improved. The restored K2 SiF6 : Mn 4+ (R‐KSFM) maintains approximately 62.3% of its initial relative emission intensity after immersing in deionized water for 300 min, while the reference commercial K2 SiF6 : Mn 4+ with a protective coating (C‐KSFM) is only 33.2%. As a proof of general applicability, this strategy was also conducted to K2 TiF6 : Mn 4+ phosphor, which is less moisture‐stable than K2 SiF6 : Mn 4+ . The luminescence intensity of the degraded K2 TiF6 : Mn 4+ (D‐KTFM) phosphor can be restored to 162.6% of original level of the K2 TiF6 : Mn 4+ synthesized through a cation exchange approach without any treatment (O‐KTFM). The emission intensity of the restored K2 TiF6 : Mn 4+ (R‐KTFM) phosphor retains 62.8% of its initial emission intensity after soaking in deionized water for 300 min. Finally, the R‐KSFM phosphors were packaged into white light‐emitting diodes with blue InGaN chips and Y3 Al5 O12 : Ce 3+ yellow phosphors. The WLEDs display excellent color rendition with higher color rendering index, lower color temperature (WLED‐II: Ra =83.6, R9 =57.3, 3743 K, ηl =199.68 lm/W; WLED‐III: Ra =90.4, R9 =94.2, 2892 K, ηl =183.3 1 m/W). The above results show that the reverse strategy can be applied in those phosphor materials with poor moisture resistance to restore luminescence properties and improve moisture resistance without excessively care about the deterioration during the production, storage and transportation. Abstract : A reverse strategy was successfully developed to restore the almost completely degraded luminescence properties of Mn 4+ ‐doped fluoride phosphors and simultaneously improve the resistance to moisture.